NURSES' KNOWLEDGE AND ATTITUDES TOWARDS PATIENT SAFETY GOALS IMPLEMENTATION IN THE PRIVATE HOSPITAL OF INDONESIA : A CROSS SECTIONAL STUDY: NURSES' KNOWLEDGE AND ATTITUDES TOWARDS PATIENT SAFETY GOALS IMPLEMENTATION IN THE PRIVATE HOSPITAL OF INDONESIA : A CROSS SECTIONAL STUDY - Tiara Amelia; Bustami; Oktizulvia, Conny (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Abstract Patient safety incidents remain a critical healthcare problem in Indonesia, particularly within hospital settings. Patient safety goals are an essential priority for healthcare providers, especially nurses, who serve as the frontline workforce delivering continuous care. Optimal implementation of patient safety goals requires adequate knowledge, supportive attitudes, and strong professional performance from nurses. Effective adherence to these goals plays a key role in preventing adverse events that may harm or endanger patients. This study aimed to examine the relationship between nurses’ knowledge and attitudes with the implementation of Patient Safety Goals in a private hospital in West Sumatra, Indonesia. A descriptive quantitative method with a cross-sectional design was used. A total of 35 nurses were selected through total sampling. Data were collected using validated questionnaires (KPSQ, APSQ, IPSG I–VI). Statistical analysis employed the Chi-Square test with a significance level of p < 0.05. Results showed that more than half of the nurses demonstrated good knowledge (51.4%), positive attitudes (57.1%), and good implementation of patient safety goals (54.3%). Chi-Square analysis revealed significant associations between knowledge and patient safety goal implementation (p=0.044<0.05), as well as between attitudes and patient safety goal implementation (p=0.012). The study concludes that nurses’ knowledge and attitudes are significantly related to the implementation of patient safety goals. Continuous training and regular dissemination regarding patient safety standards are recommended to strengthen nurses’ adherence to SOPs and to enhance the overall patient safety culture within the hospital. Keywords : Knowledge; Attitudes; Patient Safety Goals; Nurses; Hospital